المتطلبات الأساسية لنجاح برنامج الخصخصة - ديوب محمد معن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث دراسة لقضية, تعتبر من أهم القضايا المعاصرة, خصوصا بالنسبة للبلدان العربية وهي الخصخصة, فبعد النتائج السلبية لأداء القطاع العام في كثير من المجالات, نجد أن معظم الدول تتجه إلى زيادة مساهمة القطاع الخاص في الحياة الاقتصادية, وذلك عن طريق خصخصة كثير من المشروعات العامة. لذلك يركز بحثنا هذا على دراسة لموضوع الخصخصة من حيث عرض مفهومها كسياسة من سياسات الإصلاح الاقتصادي ومبرراتها الاقتصادية, كذلك الطرق التي يمكن اتباعها في مجال الخصخصة, بالإضافة إلى أهم المتطلبات لخلق البيئة المناسبة لنجاح برنامج الخصخصة في أي اقتصاد, مع عرض بعض التجارب لبلدان عربية وأجنبية في الخصخصة خاتمين البحث بعرض بعض المقترحات والتوصيات التي يمكن الاستفادة منها في ضوء تطبيق الخصخصة. This research deals with one of the most important contemporary matters, particularly for the Arab countries, which is privatization. Following the negative results of the public sector performance in many fields, we find that most of governments tend to increase the private sector contribution to the economical life through privatization of many public projects. This research focuses on studying privatization in terms of explaining its notion, its justifications, the ways which can be followed on privatization, as well as the most important requirements for creating a proper environment for successful privatization process in any economy. Furthermore, it presents some experiments of foreign and Arab country on privatization. Finally, we provide some suggestions and recommendations, which can be useful in the privatization field.